ANALISIS RASIO PROFITABILITAS PADA USAHA KERAMBA JARING APUNG BAPAK DONI DI KAMPUNG BARU - Saher, Sayid; Inggriani, Yosi; Dewi, Septira (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2023)
The importance of knowing the value of the company will be able to give a positive signal. The value can be measured which is profitability. The research method used is descriptive research with a quantitative approach. The data used are primary data and secondary data. Data analysis uses profitability ratios, namely Net Profit Margin (NPM), Turnover Of Operating Assets (TOA), Return On Equity (ROE), and Return On Investment (ROI). From mr. Doni's floating net cage business in Kampung Baru, the results of the analysis were obtained as follows: (1) The Net Profit Margin obtained in 2021 has decreased. (2) The value of Turnover of Operating Assets (TOA) obtained in 2020 was 1.78 times while in 2021 it was 2.02 times. (3) Return On Equity (ROE) obtained 0.81% to 0.77%. (4) Return On Investment (ROI) obtained in 2020 was 0.76% while in 2021 it was 0.64%.